Discovering the deep : a photographic atlas of the seafloor and ocean crust - Karson, Jeffrey A. (Cambridge : Cambridge University Press, 2015)
The deep oceans and global seafloor are truly Earth's last frontier. They remain largely unexplored, yet are critical to our survival on this planet. This magnificent, full-color volume transports you to bizarre landscapes hosting exotic life forms that rival the most imaginative science fiction. Starting with a historical summary of seafloor exploration and the developing technologies used to study this extreme environment, it then describes the distinctive geologic components of the Earth's ocean floor and the unusual biological communities found along the mid-ocean ridges. This is an indispensable reference for researchers, teachers, and students of marine science, and a visually stunning resource that will enlighten and intrigue oceanographers and enthusiasts alike. A suite of online resources, including photographs and video clips, combine with the book to provide fascinating insights into the hidden world of seafloor geology and biology using the latest deep-sea imaging and geological concepts.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Ocean bottom -- Pictorial works; Earth (Planet) -- Crust -- Pictorial works